Quasi-phase-matched high harmonic generation using trains of uniformly-spaced ultrafast pulses - O'Keeffe, K; Robinson, T; Hooker, S (2012)
We investigate quasi-phase-matching of high harmonic generation over a range of harmonic orders using trains of up to 8 uniformly-spaced counter-propagating pulses, produced using an array of birefringent crystals. © 2012 OSA.